Infectious Bronchitis Vaccination Protocols for Laying Hens - A. Sulaiman (Media Peternakan, 2011)
A research was conducted to investigate the effects of vaccination protocols for Infectious Bronchitis (IB) on egg production, egg quality, and IB antibody titres of laying hens. Different initial vaccination (Control, VicS eye, VicS spray, VicS water, A3 eye, A3 spray, and A3 water) for IB were administered to day-old Isa Brown hens. Half the hens were revaccinated regularly during lay whereas the other hens were not vaccinated. Results showed that initial vaccination treatment had significant effects on hen day egg production and egg quality of egg weight, shell reflectivity, shell breaking strength, shell thickness, albumen height, Haugh Units, and IB antibody titre levels, but had no effect on percentage of shell and yolk colour. Egg weight and shell reflectivity were less favourable in the control hens. In contrast, shell breaking strength and shell thickness were highest for the group that initially received A3 vaccine in water. However, regular revaccination had some deleterious effects on egg production and egg quality. There were no significant effects of revaccination on IB antibody titres. It is concluded that there was little advantage in regularly revaccinating laying hens for IB virus, since they had received appropriate initial vaccination.